Ineffective corporate governance: Busyness of internal board monitoring committees - Al-Yahyaee, K.; Al-Hadi, Ahmed (Virtus interpress, 2016)
We examine whether the voluntary formation of a Risk Committee (RC) compromises the effectiveness of other monitoring duties carried out by the board members. We argue that adding more monitoring committees increases the board’s internal busyness, which reduces the effectiveness of monitoring by the Audit Committee (AC). Using a sample of financial firms over the period 2007 to 2011 from the Gulf Cooperation Countries (GCC), we find that voluntarily adopting a risk committee impairs the effectiveness of the audit committee, which in turn reduces financial reporting quality. Our findings suggest that multiple layers of monitoring capacity viz-a-viz the existence of both an audit and risk committee may weaken the quality of monitoring provided by the audit committee.